2015
DOI: 10.1021/acsami.5b05865
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of Lubricant-Infused Wrinkling Surface for Preventing Thrombus Formation and Infection

Abstract: Despite the advanced modern biotechniques, thrombosis and bacterial infection of biomedical devices remain common complications that are associated with morbidity and mortality. Most antifouling surfaces are in solid form and cannot simultaneously fulfill the requirements for antithrombosis and antibacterial efficacy. In this work, we present a facile strategy to fabricate a slippery surface. This surface is created by combining photografting polymerization with osmotically driven wrinkling that can generate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 58 publications
4
80
0
Order By: Relevance
“…27 Epstein et al 11 demonstrated that IL layers on ePTFE reduced biofilm coverage of Staphylococcus aureus by 97.2% and Escherichia coli by 96% after 48 h, as well as Pseudomonas aeruginosa by 99.6% after seven days of growth under gentle flow (10 mL/min). Researchers working on IL layers fabricated using other methods have found similar results with these species both under static 27,54 and flow conditions 27,43 ( Figure 8). However, Li et al 32 found that not all bacterial strains are equally repelled by lubricantinfused surfaces.…”
Section: Bacterial Anti-adhesive Surfacesmentioning
confidence: 61%
See 1 more Smart Citation
“…27 Epstein et al 11 demonstrated that IL layers on ePTFE reduced biofilm coverage of Staphylococcus aureus by 97.2% and Escherichia coli by 96% after 48 h, as well as Pseudomonas aeruginosa by 99.6% after seven days of growth under gentle flow (10 mL/min). Researchers working on IL layers fabricated using other methods have found similar results with these species both under static 27,54 and flow conditions 27,43 ( Figure 8). However, Li et al 32 found that not all bacterial strains are equally repelled by lubricantinfused surfaces.…”
Section: Bacterial Anti-adhesive Surfacesmentioning
confidence: 61%
“…Fluorocarbon-infused wrinkled surfaces showed a 96% reduction in bovine fibrinogen deposition, a significant reduction (P < .001) in platelet adhesion and reduction in whole blood clotting time by up to 95% (correlated to antithrombogenicity) compared to controls. 54 The previously mentioned TLP coating has shown great promise in both in vitro and in vivo studies. In addition to macroscopically repelling droplets of blood on tilted surfaces (Figure 7), TLP-coated substrates showed reduced adhesion and polymerization of fibrin compared to controls, as well as Immobilized liquid layers 913 .......................................................................................................................... suppression of both adhesion and activation of platelets in in vitro thrombogenicity tests.…”
Section: Anti-thrombogenic Surfacesmentioning
confidence: 99%
“…One particular consideration is that liquid-infused surfaces significantly reduce bacterial adhesion (18,19,24,25,38), which is a key advantage in endoscopy, considering the magnitude of the tragedy at the University of California, Los Angeles Medical Center, where seven patients were infected after the procedure with Carbapenem-resistant Enterobacteriaceae due to a lack of sufficient sterilization (39). More recently, outbreaks have occurred in hospitals in Seattle, Pittsburgh, and Chicago (40).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, bioinspired slippery surfaces have been reported to effi ciently reduce thrombosis. [ 61,66 ] Leslie et al fabricated a tethered-liquid perfl uorocarbon (TLP) based slippery surface by covalently binding a fl exible molecular perfl uorocarbon layer or tethered perfl uorocarbon (TP) on material surfaces and subsequently coated with a mobile layer of perfl uorodecalin (LP) (Figure 4 b). [ 61 ] The TLP-based slippery surfaces could effectively repel whole blood, reduce fi brin polymerization, and suppress both adhesion and activation of platelets, hence confi rming their reduced thrombogenicity when contacting with fl owing whole human blood in vitro.…”
Section: Bioinspired Slippery Surfacesmentioning
confidence: 99%